2017
DOI: 10.2991/ijcis.2017.10.1.41
|View full text |Cite
|
Sign up to set email alerts
|

A new approach of multi-criteria analysis for the evaluation and selection of sustainable transport investment projects under uncertainty: A case study

Abstract: Selecting transport project to invest is an important task. This paper offers a new sustainable transport investment selection approach that applies interval-valued fuzzy sets (IVFSs) to address uncertainty. Relative preference relation is employed to address importance of criteria. Judgments of experts are given a weight based on all the gathered judgments and the expertise of experts. Furthermore, the concept of Prospect theory is used to rank the alternatives. The approach is applied to a case study and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…It can be observed that the best and the worst alternatives remain the same. However, the presented method has several advantages in comparison with the method of Ashtiani et al [38]: (1) the developed method applies Interval-Valued Pythagorean Fuzzy Set (IVPFS), one of the most powerful tools in dealing with uncertainty, to increase the 16 flexibility and ability of expressing and calculating the uncertainty in the decision problem; (2) the DMs are given a weight objectively based on the compromise solution method; and (3) the method uses an optimization model that simultaneously considers the deviation between attribute assessments and knowledge measure to address the weights of unknown criteria. This model utilizes all the available information in decision preferences and creates a comprehensive weighting approach.…”
Section:  mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that the best and the worst alternatives remain the same. However, the presented method has several advantages in comparison with the method of Ashtiani et al [38]: (1) the developed method applies Interval-Valued Pythagorean Fuzzy Set (IVPFS), one of the most powerful tools in dealing with uncertainty, to increase the 16 flexibility and ability of expressing and calculating the uncertainty in the decision problem; (2) the DMs are given a weight objectively based on the compromise solution method; and (3) the method uses an optimization model that simultaneously considers the deviation between attribute assessments and knowledge measure to address the weights of unknown criteria. This model utilizes all the available information in decision preferences and creates a comprehensive weighting approach.…”
Section:  mentioning
confidence: 99%
“…Despite all the efforts to model the uncertainty of a sustainable transportation evaluation problem in MCDM methods, most of them were based on classical fuzzy sets. In fact, there are few studies in the literature concerning sustainable transportation evaluation by using an extension of classical fuzzy sets (FSs) [12][13][14][15][16]. There is no any research carried out to discuss the problem by utilizing the Interval-Valued Pythagorean Fuzzy Set (IVPFS).…”
Section: Introductionmentioning
confidence: 99%
“…In this section to demonstrate the application steps of the introduced approach in real-world problems, an existing sustainable infrastructure project evaluation and selection problem in the literature (Mohagheghi, Mousavi, Aghamohagheghi, & Vahdani, 2017b) is adopted and solved by using the presented method. Additionally, the case deals with selecting infrastructure projects in a multi-criteria process.…”
Section: Case Studymentioning
confidence: 99%
“…Therefore, the fuzzy MCDM (FMCDM) approaches are obtained to assess the candidates in an uncertain environment (Giti-navard, Makui, & Jabbarzadeh, 2016;Gitinavard, Mousavi, & Vahdani, 2016;Gitinavard, & Zarandi, 2016). Furthermore, establishing a group of specialists for appraising the problem under imprecise information is lead the FMCDM approaches to fuzzy multi-criteria group decision-making (FMCGDM) approaches (e.g., Mohagheghi, Mousavi, Aghamohagheghi, & Vahdani, 2017;Mohagheghi, Mousavi, Vahdani, & Siadat, 2017;Mohagheghi, Mousavi, & Vahdani, 2017a, 2017bZolfaghari & Mousavi, 2018).…”
Section: Introductionmentioning
confidence: 99%